A porous two-dimensional Zn(ii)-coordination polymer exhibiting SC–SC transmetalation with Cu(ii): efficient heterogeneous catalysis for the Henry reaction and detection of nitro explosives. Issue 23 (5th June 2017) - Gupta, Mayank; De, Dinesh; Pal, Sanchari; Pal, Tapan K.; Tomar, Kapil
Abstract : The 2D Zn(ii )-CP, 1Zn and its Cu-analogue1Cu exhibit efficient catalytic activity for the Henry reaction.1Zn can be utilized for detecting trace amounts of nitro explosives in DMSO. Abstract : The linker 5-(benzylamino)isophthalic acid (H2 L ) forms a robust 2D Zn(ii )-coordination polymer, [Zn8 (L )6 (μ3 -OH)4 (H2 O)6 ]·(DMF)·(H2 O)2.5 n (1Zn ) consisting of [Zn4 (μ3 -OH)2 ] 6+ SBUs. It further shows strong π⋯π interactions between the layers to form an overall 3D structure with well-defined channels. Metal bound water molecules are directed towards these channels. Upon heating, these metal bound water molecules are lost along with lattice solvent molecules to afford coordinatively unsaturated metal centers that can be utilized as an efficient heterogeneous catalyst for the C–C bond forming nitroaldol or Henry reaction. The solid catalyst can be recycled at least three times without losing its catalytic activity. The easily accessible channels in1Zn are found suitable for the SC–SC transmetalation reaction with Cu(ii ) producing1Cu . The catalytic activity of1Cu is found to be comparable to that of1Zn . Furthermore, the framework1Zn gives high emission in DMSO, which can be efficiently quenched by trace amounts of nitro explosives. All the complexes have been characterized by single crystal X-ray diffraction, powder X-ray diffraction, IR, thermogravimetry and elemental analysis.